Characterization, antimicrobial and catalytic activities of silver nanoparticles biosynthesized using aqueous extract of Euphorbia graminea (2023)
Phytosynthesis of silver nanoparticles (AgNPs) is not only affordable and ecofriendly but provides a means of synthesizing phytochemical capped AgNPs with predefined characteristics. The objective of this study was the green synthesis of AgNPs that possess antimicrobial and catalytic activities using aqueous extract of Euphorbia graminea. Reactions parameters critical to the yield, size and morphology of the biosynthesized AgNPs were optimized using UV spectroscopy. The UV-visible spectra analysis of the biosynthesized AgNPs showed surface plasmon resonance occurred at 462 nm. Scanning Electron Microscopy with Energy dispersive X-ray analysis revealed the characteristic absorption band of AgNPs at 3 KeV and confirmed 73.66% composition of particles as metallic silver. The AgNPs appeared as well-separated, quasi-spherical particles with narrow size distribution of 6.77±0.89 nm when examined with Transmission electron microscopy. X-ray diffraction confirmed the crystallinity of the AgNPs with mean crystallite size of 7.65 nm. The biosynthesized AgNPs showed broad-spectrum antimicrobial activity against bacteria and fungi. The rate constant of the degradation of methylene blue in the presence of as-synthesized AgNPs was increased several folds to sec-1 from sec-1 in its absence. The prepared AgNPs could find applications as therapeutic coats in medical devices and in effluent treatment of chemical industries.